Motivational factors from citizens participating in civic crowdsourcing initiatives (2017)
Abstract. The perspective of citizen participation via electronic means is a topic that is taking relevance in the recent years from governments in order to find new ways to engage citizens in a more direct dialogue about public matters. This research study is based on the motivational drivers of citizens around a civic crowdsourcing model in order to strengthen the guidelines of open government and e-government in Bogotá. For this, first it was characterized a civic crowdsourcing initiative in Bogotá. Then, it was gathered motivational user crowdsourcing dimensions from the literature review to set up a survey-based analysis. Afterwards, an explorative factor analysis and clustering analysis was run to profile the most relevant motivational drivers in the studied population. Finally, it was described the data of clusters and interpreted against the literature.